EXPLORING THE ROLE OF GUT MICROBIOTA IN DIFFERENT BEE SPECIES AND THE PESTICIDE PARADOX - Mohammad Ikram; Srinivasan M. R.; Suganthi A; Marta Guarna M; Saminathan V. R.; Auxcilia J; Jayakanthan M; Bimal Kumar Sahoo; Kiruthika K; Senthil Kumar M; Sivasankari Sivakumar; Lalremliana; et al. (Journal of Animal and Plant Sciences, 2026)
Bee populations worldwide are declining, posing a threat to biodiversity and food security. Bees including both Apis and non-Apis species frequently encounter various pesticides, including herbicides, fungicides, and insecticides during nectar and pollen foraging. Pesticide toxicity has been associated with a variety of health issues in bees, including metabolic diseases, immune system problems, neurotoxicity, and reproductive disorders. All bee species harbor microorganisms in their gut which play a significant role in their health and function, but can also be affected by environmental stressors including pesticides. Understanding the intricate relationship between bee gut microbiota and pesticide exposure is crucial for addressing pesticide toxicity crisis. This review explores the pivotal role of gut microbiota in bee’s susceptibility to pesticides, highlighting the pesticide paradox - how chemicals intended to protect crops, can harm beneficial insects like bees. The impact of pesticides on gut microbiota composition and function, the synergetic role of detoxifying enzymes and gut microbiota in mitigating pesticide toxicity is discussed.
Keywords: Detoxifying enzymes; gut microbes; bees; immunity; metabolism; pesticides